2011
DOI: 10.1007/s12519-011-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity associated with inflammation in their children

Abstract: These results suggest that maternal obesity during pregnancy is associated with later development of elevated hs-CRP in the offspring, even after controlling for weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…Likewise, maternal obesity in sheep and non-human primates has been shown to induce inflammation in the placenta, fetal liver, heart and intestine (2628). The placenta in obese women is likewise characterized by inflammation and associated with increased systemic LPS levels (2932). Our previous studies demonstrated activation of JNK and NF-κB pathways in placenta from obese women (33).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, maternal obesity in sheep and non-human primates has been shown to induce inflammation in the placenta, fetal liver, heart and intestine (2628). The placenta in obese women is likewise characterized by inflammation and associated with increased systemic LPS levels (2932). Our previous studies demonstrated activation of JNK and NF-κB pathways in placenta from obese women (33).…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, there is evidence that prepubescent children of women who were obese during pregnancy were dramatically more likely to have detectable C-reactive protein levels than children of non-obese mothers, even after controlling for the child's BMI and other potential confounding factors. 42 There is convincing evidence that intrauterine inflammation and fetal systemic inflammation are associated with an increased risk of brain injury leading to neurodevelopmental disability, such as cerebral palsy. 43,44 It is possible that the potential effects of increased inflammation in obese women, even in the absence of clinical signs or symptoms, is sufficient to significantly alter brain development in some children.…”
Section: Discussionmentioning
confidence: 99%
“…1 Limitation in intellectual ability corresponds to an intelligence quotient (IQ) of <70, described as mild (IQ 55-70), moderate (IQ [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], or severe to profound (IQ of <40). 2 The prevalence of ID in the general population is estimated to be approximately 1%, and among those with ID 85% are characterised as having mild ID.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of publications indicate that maternal obesity can result in chronic inflammation and oxidative stress [7]. These conditions may, for example, impair placentation and establishment of adequate blood supply, perhaps altering fetal metabolism [8].…”
Section: How Do Maternal Obesity and Diet Influence The Early Nutritimentioning
confidence: 99%